Transdisciplinary STEM: Examples of Student Thinking within Nonformal Learning Experiences - Kristin Lesseig; David Slavit; Amber Simpson (MDPI AG, 2023)
Calls for more integrated approaches to STEM have reached every sector of education, including formal and nonformal spaces, from early childhood to tertiary levels. The goal of STEM education as an integrated effort shifts beyond acquiring knowledge in any one or combination of STEM disciplines and, instead, focuses on designing solutions to complex, contextual problems that transcend disciplinary boundaries. To realize this goal, we first need to understand what transdisciplinary STEM might actually look and sound like in action, particularly in regard to the nature of student thinking. This paper addresses that need by investigating student reasoning during nonformal STEM-focused learning experiences. We chose four learning episodes, all involving elementary students working on engineering design tasks, to highlight the various ways transdisciplinary thinking might arise or not. In our analysis, we highlight factors that may have supported or hindered the integration of mathematical, scientific, technological, and engineering ways of thinking. For example, the nature of the task, materials provided, and level of adult support influenced the nature of student reasoning. Based on our findings, we provide suggestions for how to promote transdisciplinary thinking in both formal and nonformal spaces.